The battle of hashtag on Twitter: Unraveling the pioneers of influence in social media marketing - Bate, Andi Pajolloi; Prasetyo, Kurniawan (Universitas Bunda Mulia, 2024)
This research aims to identify Key Opinion Leaders (KOLs) in hashtag marketing campaigns on social media using Social Network Analysis (SNA) method. The study explores the social network formed in the campaign between #TimPakeSendok and #TimPakeTangan to identify influential users who play a significant role in the dissemination and reach of the campaign based on degree centrality, betweenness centrality, and eigenvector centrality analysis. The study finds that actors with many followers on Twitter tend to have high centrality levels, both in terms of degree centrality, betweenness centrality, and eigenvector centrality, indicating that they are actively connected to other actors in the network, act as effective intermediaries between other actors, and have meaningful connections with other influential actors in the network during this hashtag marketing campaign. However, the closeness centrality measurement indicates that actors with significant closeness centrality are those with fewer followers. Other findings show that sharing opinions and interacting with other users in the hashtag campaign create a sense of togetherness and affinity within groups with similar interests.